Nano-MgO and nanostructured ZnO/MgO films: topology, morphology and dielectric properties / Habibah Zulkefle ... [et al.] - Zulkefle, Habibah; Mohd Dahan, Rozana; Mamat, Mohamad Hafiz; Mahmood, Mohamad Rusop (UiTM Press, 2024)
High leakage current and low dielectric constant, k has been reported as drawback of commercialize dielectric material which leads to the exploration of new dielectric materials. In this study, nano-MgO films and nanostructured ZnO/MgO bilayer dielectric films were synthesized using sol-gel spin coating method and deposited at various MgO solution concentration. The uniform nano-ZnO film was utilized as the oxide dielectric template to produce nanostructured ZnO/MgO bilayer films. The effect of MgO solution concentration towards topology, morphology and dielectric properties of nano-MgO films and nanostructured ZnO/MgO bilayer films were investigated. The variation of solution concentrations revealed that nano-MgO film and nanostructured ZnO/MgO bilayer film with 0.4 M MgO concentration produced improvement in the dielectric properties (dielectric constant, k) which is 4.9 and 5.71 respectively. This is caused by the uniform particle distributions and well-defined structure produced in these films. Besides, the bilayer film structure (nanostructured ZnO/MgO bilayer films) was found to produce slightly higher k value in comparison to single layer structure (nano-MgO films).